Avaliação pré-clínica de esteroide anabólico androgênico como indutor de distúrbios comportamentais, ovarianos, uterinos e reprodutivos - Barcelos, Mônica Naves (2024)
Prolonged and excessive consumption of Anabolic Androgenic Steroids (AAS) causes pathological changes in vital organs such as the heart and in other body systems such as the reproductive, renal and hepatic systems. Currently, there is a growing trend regarding the use of AAS, mainly indiscriminately, that is, without specialist monitoring. Despite the benefits that its use can provide, there is evidence that proves that the excessive use of anabolic steroids causes reversible and often irreversible damage, such as death. The objective of this study was to evaluate the use of testosterone 17ȕ-cyclopentylpropionate in disorders of the female reproductive system. For this purpose, female mice were used that were medicated with the androgen and then sacrificed so that their reproductive organs could be analyzed. Doses of 5, 10 and 20 mg/kg of testosterone 17ȕ-cyclopentylpropionate were applied to female mice and the results showed its influence on the female reproductive system.